IMPLEMENTATION LEARNING MODEL COOPERATIVE COURSE REVIEW HORAY (CRH) WITH TALKING STICK TO STUDENT LEARNING OUTCOMES - Ririn Amaliah Putri Sarah; Ahmad Fauzan Yusman; Alwen Bentri; Darmansyah Darmansyah (Research and Development Journal of Education, 2023)
Education is one aspect thatxplays a very important role in development. One important part of the education system is the teaching and learning process in schools. Thexpurpose of this study was to determine the increase in student learning outcomes to the learningxmodel Course Review Horay (CRH withxTalking Stick at SMP Negeri 2 Batang Anai. The research method used is the experimental method (quasi experiment). The subjects of this study were students of class VIII.3 as the experimental class who were treated with thexlearning model Course ReviewxHoray (CRH) with Talking Stick, and students of class VIII.5 as the class that used the conventional control model. The data analysis technique used is the t-test. Based on the research that has been done, the learning outcomes of students who apply the learning model Course Review Horay (CRH) with Talking Stick with the traditional model are t count = 2.454 > ttable = 2.024. Data on student learning outcomes using Cooperative Learning Type Course ReviewxHoray with Talking Stick with the application of the traditional model obtained tcount = 2.454 > ttable = 2.024. In conclusion, thexapplication of Course Review Horay with the type of collaborative learning with TalkingxStick has a significant effectxon the learning outcomes of class VIII IPA students of SMP Negeri 2 Batang Anai